2019
DOI: 10.1038/s41598-019-44407-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A inhibits tumor mutator APOBEC3B through phosphorylation

Abstract: APOBEC3B cytidine deaminase (A3B) catalyzes cytosine into uracil in single-strand DNA and induces C-to-T mutations in genomic DNA of various types of tumors. Accumulation of APOBEC signature mutations is correlated with a worse prognosis for patients with breast cancer or multiple myeloma, suggesting that A3B activity might be a cause of the unfavorable DNA mutations and clonal evolution in these tumors. Phosphorylation of conserved threonine residues of other cytidine deaminases, activation induced deaminase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Nonetheless, these results indicate that deaminase activity is dispensable for the effects mediated by A3B in MNNG-treated cells. Deaminase independent activity has been found in other instances of A3-mediated effects including A3B [40][41][42][43][44][45] . We also found that knockdown of endogenous A3B by siRNA did not affect the level of γ-H2AX foci ( Supplementary Fig.…”
Section: A3b Enhances Mnng-induced γ-H2ax Foci In Hs578t Cells By a Dmentioning
confidence: 96%
See 1 more Smart Citation
“…Nonetheless, these results indicate that deaminase activity is dispensable for the effects mediated by A3B in MNNG-treated cells. Deaminase independent activity has been found in other instances of A3-mediated effects including A3B [40][41][42][43][44][45] . We also found that knockdown of endogenous A3B by siRNA did not affect the level of γ-H2AX foci ( Supplementary Fig.…”
Section: A3b Enhances Mnng-induced γ-H2ax Foci In Hs578t Cells By a Dmentioning
confidence: 96%
“…A3B, like other members of the A3 family, is a single-strand specific DNA binding protein 44,55 . This property is presumably related to the numerous instances of A3 deaminase-independent effects [40][41][42][43][44][45] . Thus, our findings that A3B deaminase activity is not required for its aggravation of MNNGinduced DSBs suggest that it does so as a consequence of binding to the single-stranded regions that characterize MNNG-induced damage, perhaps by interfering with or delaying the eventual repair of these lesions.…”
Section: Fate Of O 6 Meg/c-containing Plasmid Dna In Hs578t Cellsmentioning
confidence: 99%
“…Ras mutations are mostly subclonal and detected at the time of both diagnosis and relapse [16,18,22,36], consistent with their role in tumor progression but not the initiation of MM. Little is known about the mechanisms underlying the acquisition of non-synonymous point mutations in Ras family oncogenes by MM cells; however, the involvement of the APOBEC3B cytidine deaminase was suggested by a recent comprehensive analysis of the mutation signature of multiple cancers [37][38][39] and subsequent biochemical studies [40,41]. APOBEC3B confers hypermutator phenotypes to cancer cells by converting cytidine to uracil/thymidine in TCN trinucleotide repeats in the genome [40][41][42].…”
Section: Genetic Abnormalities Driving the Progression Of Mgus To MMmentioning
confidence: 99%
“…Little is known about the mechanisms underlying the acquisition of non-synonymous point mutations in Ras family oncogenes by MM cells; however, the involvement of the APOBEC3B cytidine deaminase was suggested by a recent comprehensive analysis of the mutation signature of multiple cancers [37][38][39] and subsequent biochemical studies [40,41]. APOBEC3B confers hypermutator phenotypes to cancer cells by converting cytidine to uracil/thymidine in TCN trinucleotide repeats in the genome [40][41][42]. This enzyme has been demonstrated to be a transcriptional target of Maf transcription factors and may contribute to rapid progression and treatment resistance of MM cases carrying t (14;16) and t (14;20) [37,42].…”
Section: Genetic Abnormalities Driving the Progression Of Mgus To MMmentioning
confidence: 99%
See 1 more Smart Citation